Spinal fusion in facioscapulohumeral dystrophy for hyperlordosis: A case report - Eren, İlker (Medicine (Baltimore), 2020)
RATIONALE: Facioscapulohumeral muscular dystrophy (FSHD) is the third most common muscular dystrophy, which is associated with facial, shoulder girdle, and paraspinal muscle atrophy. Most of the patients develop hypokyphosis and hyperlordosis in the course of the disease, to preserve standing posture. Corrective fusion is contraindicated in these patients as the surgery results with loss of compensatory hyperlordosis and leads to loss of trunk balance while standing. Although spinal fusion in neuromuscular scoliosis is a known treatment option, there are no studies in the literature on the spinal fusion of this specific patient group. PATIENT CONCERNS: In this case report we have presented a 66-year-old woman, who was admitted with back and abdominal pain, inability to sit straight, abdominal discomfort, and numbness in the lower extremities after prolonged sitting. DIAGNOSES: The patient developed severe hyperlordosis causing intra-abdominal disorders, radicular symptoms, and sitting discomfort due to FSHD. INTERVENTIONS: The patient underwent T2–S1 fusion and successful fusion was achieved. OUTCOMES: Individualized Neuromuscular Quality of Life Questionnaire (INQoL) was used to assess preoperative and 3 years postoperative functional outcomes. All domains and total score improved at the end of the follow-up period and successful fusion was verified radiologically. LESSONS: This case suggests that spinal fusion may provide functional improvement in carefully selected patient groups. Patient stratification considering spinal disability is required for further studies in this specific indication.